2020
DOI: 10.1042/bsr20191517
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-based proteomics analysis on insomnia rats treated with Mongolian medical warm acupuncture

Abstract: Objective: To explore the proteomic changes in the hypothalamus of rats treated with Mongolian medical warm acupuncture for insomnia therapy based proteomics. Method: We used an iTRAQ-based quantitative proteomic approach to identify proteins that potential molecular mechanisms involved in the treatment of insomnia by Mongolian medical warm acupuncture. Result: In total, 7477 proteins were identified, of which 36 proteins showed increased levels and 45 proteins showed decreased levels in insomnia model group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…KEGG pathway enrichment analysis can help us further figure out the potential pathways of ZSS against insomnia; after all core genes are entered and after applying p value significance selection criteria, 44 genes from all clusters are systematically selected and 19 representative pathways are selected ( p < 0.01 p < 0.01), as shown in Figure 5(a) , and these pathways are divided into 7 categories by signaling pathway functional clustering analysis, of which neuroactive ligand-receptor interaction (KEGG:04080), AGE-RAGE signaling pathway in diabetic complications (KEGG:04933), dopaminergic synapse (KEGG:04728), cAMP signaling pathway (KEGG:04024), synaptic vesicle cycle (KEGG:04721), serotonergic synapse (KEGG:04726), and cholinergic synapse (KEGG: 04725) each represent a class of biological pathways ( Figure 5(b) ). Some of these pathways have been shown to be highly connected with insomnia, such as key protein pathways that upregulate neuroactive ligand-receptor interaction signaling that can significantly improve insomnia [ 35 ], and some pharmacological treatments for psychiatric disorders also use selective blockade of presynaptic dopamine receptors in the frontal cortex, enhancing dopaminergic transmission, which is consistent with the results of our analysis of modulation of the dopaminergic synapse signaling pathway [ 36 ]. All details of the KEGG pathway enrichment analysis are described in Supplementary Table S6 .…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…KEGG pathway enrichment analysis can help us further figure out the potential pathways of ZSS against insomnia; after all core genes are entered and after applying p value significance selection criteria, 44 genes from all clusters are systematically selected and 19 representative pathways are selected ( p < 0.01 p < 0.01), as shown in Figure 5(a) , and these pathways are divided into 7 categories by signaling pathway functional clustering analysis, of which neuroactive ligand-receptor interaction (KEGG:04080), AGE-RAGE signaling pathway in diabetic complications (KEGG:04933), dopaminergic synapse (KEGG:04728), cAMP signaling pathway (KEGG:04024), synaptic vesicle cycle (KEGG:04721), serotonergic synapse (KEGG:04726), and cholinergic synapse (KEGG: 04725) each represent a class of biological pathways ( Figure 5(b) ). Some of these pathways have been shown to be highly connected with insomnia, such as key protein pathways that upregulate neuroactive ligand-receptor interaction signaling that can significantly improve insomnia [ 35 ], and some pharmacological treatments for psychiatric disorders also use selective blockade of presynaptic dopamine receptors in the frontal cortex, enhancing dopaminergic transmission, which is consistent with the results of our analysis of modulation of the dopaminergic synapse signaling pathway [ 36 ]. All details of the KEGG pathway enrichment analysis are described in Supplementary Table S6 .…”
Section: Resultssupporting
confidence: 80%
“…KEGG pathway analysis effectively helps us to associate genomes with cellular, species, and ecosystem functions. According to the results of our analysis, neuroactive ligand-receptor interaction, cAMP signaling pathway, and one of the key pathways to treat insomnia in ZSS, in the pathway, multiple targets such as ADRA1A, ADRA1B, and ADRA1D can be simultaneously regulated by components such as (S)-cointeraction, sanjoinenine, and zizyphusine, and upregulation of neuroactive ligand-receptor interaction has also been an active process for the treatment of insomnia [ 35 ]. Besides identifying the specific pathways involved, cluster analysis of these pathways is also unique to our study, such as the cAMP signaling pathway, renin secretion, and dopaminergic synapse; these three pathways function similarly or are more closely linked during ZSS treatment of insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Isobaric tags for relative and absolute quantitation (iTRAQ) is an isobaric labelling method. It has often been used in acupuncture studies to identify biomarkers and to elucidate potential mechanisms for the treatment of diseases [21][22][23]. However, quantitative proteomics is seldom to study of the mechanism of acupuncture treatment in T2DM with NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Conjoint analysis of transcriptome and metabolome revealed that the most remarkably enriched pathway for differential genes enrichment is the neuroactive ligandreceptor interaction pathway, which is enriched to 19 genes and five metabolites. Bioinformatics analysis showed that upregulation of neuroactive ligand-receptor interactions improved sleep (28). The most noticeably enriched pathway for differential metabolites enrichment is the GABAergic synapse pathway, which is upregulated and enriched to four metabolites and two genes.…”
Section: Discussionmentioning
confidence: 99%